Dissolved rare earth elements, shale-normalized patterns, biogeochemical parameters, and indices from molecular analysis of dissolved organic matter across the land-ocean continuum in the German Bight - Corinna Mori; Olaf Dellwig; Melanie Beck; Roger Carvalho da Silva; Thorsten Dittmar; Linn Speidel; Jochen Wollschläger; Michael Siedel (PANGAEA, 2025)
We analyzed concentrations of dissolved rare earth elements (REE) across the land-ocean continuum in the German Bight (southern North Sea) to identify key drivers for REE cycling in dynamic coastal environments. We identified the coastal transition zone as a critical interface for altering predominantly riverine-derived natural and anthropogenic REEs. We combined shale-normalized REE patterns, measured by quadrupole inductively coupled plasma-mass spectrometry (Q-ICP-MS), with biogeochemical bulk parameters and molecular analysis of dissolved organic matter (DOM) determined by ultrahigh-resolution mass spectrometry (FT-ICR-MS). Samples were acquired during RV Heincke cruise HE527. The dataset includes spatially resolved biogeochemical data (concentrations of chlorophyll-a, dissolved nitrogen, dissolved organic carbon, suspended particulate matter, dissolved iron, dissolved manganese and dissolved REE) in surface waters obtained along the major estuarine transects (Ems, Weser, and Elbe), coast-orthogonal transects and an offshore North Sea transect, with additional deep-water samples. Temporally resolved data were collected near the barrier islands Langeoog and Spiekeroog including the Otzumer Balje inlet. The dataset also contains molecular indices based on DOM composition (see Speidel et al., 2024) REE subgroups, ratios and concentrations of anthropogenic Samarium and Gadolinium (for details see Mori et al., 2025).